Optimal homeostatic stress to maximize the homogeneity of adaptations to interval interventions in soccer players - Sheykhlouvand, Mohsen; Gharaat, Mohammadali (Frontiers in Physiology, 2024)
This study examined the uniformity of adaptations in cardiorespiratory fitness and bio-motor abilities by analyzing individual responses to measures representing the mentioned qualities.Twenty-four male well-trained soccer players (Age = 26±4 years; stature = 181±3.8; Weight = 84±6.1) were randomized to two groups performing short sprint interval training [sSIT (3 sets of 10×4 sec all-out sprints with 20 seconds of recovery between efforts and 3 minutes of rest intervals between sets)] or a time-matched small-sided game [SSG (3 sets of 3 v 3 efforts in a 20×15 m area with 3 minutes of relief in-between)]. Before and after the 6-week training period, aerobic fitness indices, cardiac hemodynamics, and anaerobic power were assessed through a graded exercise test utilizing a gas collection system, noninvasive impedance cardiography, and a lower-body Wingate test, respectively. Also, sport-specific bio-motor abilities were determined by measuring linear speed, change of direction, and jumping ability. Comparing inter-individual variability in the adaptive changes by analyzing residuals in individual adaptations indicated that sSIT induces more uniform changes in the first and second ventilatory threshold (VT1 & VT2), stroke volume, and peak power output across team members than SSG. SSG also yielded lower proportions of responders in V ̇O2max, VT1, VT2, peak, and average power output compared to sSIT. Additionally, the coefficient of variation in mean group changes in measures of aerobic fitness and bio-motor abilities in response to sSIT were lower than in SSG. Short sprint interval training induces more homogenized adaptations in measures of cardiorespiratory fitness and anaerobic power than smallsided games across team members.